Fruit and seed development in two Hakea species (Proteaceae) - Groom, Philip; Lamont, Byron (2004)
Hakea erinacea and H. trifurcata are related taxa that release their annual seed crop within a year of fruit maturity (weak serotiny). Both species produce similar-sized woody fruits (follicles) that protect two winged seeds. Fruit and seed development was completed 180 days (H. erinacea) and 215 days (H. trifurcata) after anthesis, with the fruits of both species reaching their maximum fresh mass during their ‘green’, non-woody state. This was associated with the commencement of wood formation in their fruit walls and the redistribution of certain nutrients (particularly phosphorus) from the fruit to developing seeds. Both H. erinacea and H. trifurcata retain chlorophyll in the walls of developing fruit, with H. trifurcata retaining chlorophyll in the mature fruit. This may have antiherbivore properties whereby the developing green fruits are cryptically disguised within a background of similarly green leaves.